Serum Uric Acid Is a Mediator of the Association Between Obesity and Incident Nonalcoholic Fatty Liver Disease: A Prospective Cohort Study - Zhang, Qian; Ma, Xiaoqian; Xing, Jie; Shi, Haiyun; Yang, Runkuan; Jiao, Yue; Chen, Shuohua; Wu, Shouling; Zhang, Shutian; Sun, Xiujing (Frontiers in Endocrinology, 2021)
Objective: Obesity has been demonstrated to show a consistent link with the increased possibility of nonalcoholic fatty liver disease (NAFLD). Since both serum uric acid (SUA) and obesity are essential components of metabolic syndrome (MetS), it is uncertain whether the incidence of NAFLD results from serum uric acid, obesity, or other potential factors based on previous studies. Patients and methods: This study enrolled 16,839 participants with no history of alcohol consumption and no fatty liver disease in 2010. All participants completed a survey which included health and lifestyle questionnaires, and underwent physical examination, ultrasonography, and laboratory examinations of blood samples. After the four-year follow up, 5,104 (30.31%) participants were diagnosed with NAFLD. The associations between SUA, BMI or obesity, and incident NAFLD were assessed by multivariate linear regression, logistic regression analysis, and mediation analysis, respectively. Results: By adjusting demographic and serum characteristics, the linear correlation coefficients between obesity and SUA were 20.26 [95% confidence interval (CI)]: 15.74, 24.77), 13.31 (95% CI: 6.63, 19.99) and 22.21 (95% CI: 16.41, 28.02) in the total population, and in the female and male groups, respectively. The odds ratios were 2.49 (95% CI: 1.61, 3.87) in the total population, 5.71 (95% CI: 2.25, 14.45) in the female group and 1.99 (95% CI: 1.15, 3.45) in the male group for the correlation between obesity and incident NAFLD. Mediation analysis showed that SUA contributed to 10.03%, 0.58%, and 12.54% of obesity-related NAFLD development in the total population, females and males, respectively. Conclusion: The findings showed mediation linkages of both obesity and SUA with the incident NAFLD. The role of SUA as a mediator constitutes clinical significance that should be recognized and considered.